An efficient metal-free bifunctional oxygen electrocatalyst of carbon co-doped with fluorine and nitrogen atoms for rechargeable Zn-air battery. (20th March 2020) - Zhu, Ping; Gao, Jingxia; Chen, Xiaowen; Liu, Sa
Abstract: It is highly critical to explore efficient bifunctional oxygen electrocatalysts for regenerative fuel cells and metal-air batteries. Herein, N, F co-doped carbon material (NF@CB) was synthesized as metal-free efficient bifunctional electrocatalysts by directly pyrolyzing a mixture of carbon black, polytetrafluoroethylene and melamine. Benefiting from the synergistic effects between N and F atoms, NF@CB exhibits a positive half-wave potential ( E 1/2 ) of 0.814 V (vs. RHE) for oxygen reduction reaction, and an operating potential ( E 10 ) of 1.609 V at 10 mA cm −2 for oxygen evolution reaction in alkaline electrolyte. The bifunctional oxygen electrocatalytic activity index (Δ E = E 10 − E 1/2 ) is 0.795 V, which is notably better than that of the single N-doped carbon (1.238 V), and similar to that of the commercial Pt/C and RuO2 mixture catalyst (0.793 V). Impressively, the assembled Zn-air battery (ZAB) with NF@CB as an air-electrode catalyst displays a small charge/discharge voltage gap of 0.852 V at 20 mA cm −2 . Moreover, the NF@CB catalyzed ZAB exhibits good rechargeability and long-lasting cycling stability with over 49 h. This investigation introduces a cheap and simple way to develop highly efficient bifunctional N, F co-doped electrocatalysts. Graphical abstract: Image 1 Highlights: NF@CB was prepared as a metal-free catalyst via a facile synthesis method. NF@CB showed excellent catalytic activity for both ORR and OER in alkaline media. NF@CB catalyzed ZABs showed outstanding rechargeability and cycling stability.